SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA PEGAWAI DAN GURU MENGGUNAKAN METODE SAW: DECISION SUPPORT SYSTEM, PHP, SIMPLE ADDITIVE WEIGHTING, SQLYOG. - Furnawan, Hambali; Ra?afi Pratama, Muhammad (LP2M STMIK Nurdin Hamzah Jambi, 2017)
SD Negeri I / IV Kota Jambi is one of the favorite elementary schools in Jambi City. In order to improve the quality of education services to students, the school regularly evaluates the performance of teachers and employees. Assessment is done by measuring the performance of each teacher and employees in carrying out their duties and obligations, in accordance with existing competencies. During this time, the implementation of teacher performance evaluation in SD Negeri I / IV of Kota Jambi is done using form sheets that filled manually. The decision support system with the SAW (Simple Additive Weighting) method is built to assist the school in determining the performance appraisal of teachers and employees effectively and efficiently. There are 10 criteria used in the assessment (C1-C10) with a weight of importance level of 1 to 5. The ranking is done by looking at the preference values ??of each alternative (ie teachers and employees). This decision support system is built on the web using PHP programming language with SQLYog database. The application of decision support system is expected to help the school to assess the performance of employees and teachers more efficiently.